RESEARCH PAPER STRUCTURE – ORGANIZATIONAL AND ECONOMICFACTORS INFLUENCING THE COMPETITIVENESS OF HOTEL ENTERPRISES (Scientific Journal of Actuarial Finance and Accounting, 2025)
This study investigates the organizational and economic factors influencing the competitiveness of hotel enterprises in emerging tourism economies. The main objective is to identify how internal management practices and external economic conditions jointly affect hotel performance and strategic positioning. Employing a quantitative comparative analysis, data were collected through structured surveys from five hotel enterprises and analyzed using statistical and graphical tools. The research findings reveal that high organizational capacity—characterized by strong leadership, innovation, and employee competence—significantly contributes to competitive advantage, particularly when coupled with favorable economic factors such as inflation stability, access to capital, and labor market efficiency. The theoretical contribution of the study lies in integrating both organizational and economic perspectives within a single analytical framework, an approach less explored in existing hospitality research. The implications are relevant for hotel managers aiming to optimize internal capabilities, as well as policymakers developing tourism support strategies. However, the study is limited by the sample size and geographic concentration, suggesting the need for broader, cross-regional research to validate and expand upon these insights.